2016
DOI: 10.1142/s0217984916501529
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of Mg(0001)/MgO(1-11) interfaces

Abstract: By means of first-principles density-functional calculations, we studied the surface energy of a nonstoichiometric MgO(1-11) slab, the interfacial energy and interfacial bonding characteristics of Mg-terminated and O-terminated Mg/MgO(1-11) interfaces with three stacking-site (TOP, HCP and FCC sites) models, and the effect of the thickness of Mg films on the O-terminated MgO(1-11) surface. The results indicate that the surface energies of the nonstoichiometric MgO(1-11) slab and interfacial energies of Mg/Mg(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 37 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…This suggests that fcc MgO can act as sites for heterogeneous nucleation of hcp a-Mg. First-principles approaches were used to explore mainly the wetting and adhesion for different crystal orientations between solid a-Mg and MgO. [20][21][22] In order to understand the structural effect on prenucleation at atomic level, Men and Fan [23,24] performed atomistic molecular dynamics (MD) simulations on the atomic ordering in a liquid metal adjacent to a smooth substrate of different lattice misfits. Their simulations showed that the structural effect is strong on the in-plane atomic ordering but weak on the atomic layering in the liquid adjacent to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that fcc MgO can act as sites for heterogeneous nucleation of hcp a-Mg. First-principles approaches were used to explore mainly the wetting and adhesion for different crystal orientations between solid a-Mg and MgO. [20][21][22] In order to understand the structural effect on prenucleation at atomic level, Men and Fan [23,24] performed atomistic molecular dynamics (MD) simulations on the atomic ordering in a liquid metal adjacent to a smooth substrate of different lattice misfits. Their simulations showed that the structural effect is strong on the in-plane atomic ordering but weak on the atomic layering in the liquid adjacent to the substrate.…”
Section: Introductionmentioning
confidence: 99%